2015
DOI: 10.1002/clc.22373
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Major Bleeding in Patients With Nonvalvular Atrial Fibrillation: A Pharmacovigilance Study of 27 467 Patients Taking Rivaroxaban

Abstract: Background:In nonvalvular atrial fibrillation (NVAF), rivaroxaban is used to prevent stroke and systemic embolism. Objective: To evaluate major bleeding (MB) in NVAF patients treated with rivaroxaban in a real-world clinical setting. Methods: From January 1, 2013, to March 31, 2014, US Department of Defense electronic health care records were queried to describe MB rates and demographics. Major bleeding was identified using a validated algorithm. Results: Of 27 467 patients receiving rivaroxaban, 496 MB events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
95
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 15 publications
11
95
3
7
Order By: Relevance
“…A similar relationship, as in the aforementioned studies reporting the relationship between the CHADS 2 risk score and the rate of major bleeding, was also described in a recent analysis of the large database of the United States Department of Defense concerning electronic medical records of 27,467 patients with AF treated with rivaroxaban between February 1, 2013 and March 31, 2014 17 . The mean CHADS 2 score was 2.2 and 496 major bleeding events were recorded in 478 patients, a rate of 2.86% per person years.…”
Section: Conflict Of Interest: Nonesupporting
confidence: 71%
“…A similar relationship, as in the aforementioned studies reporting the relationship between the CHADS 2 risk score and the rate of major bleeding, was also described in a recent analysis of the large database of the United States Department of Defense concerning electronic medical records of 27,467 patients with AF treated with rivaroxaban between February 1, 2013 and March 31, 2014 17 . The mean CHADS 2 score was 2.2 and 496 major bleeding events were recorded in 478 patients, a rate of 2.86% per person years.…”
Section: Conflict Of Interest: Nonesupporting
confidence: 71%
“…These factors include certain types of solid tumors such as gastric, neck or lung cancer, thrombocytopenia, platelet dysfunction, prior surgeries, metastatic disease, myelosuppressive chemotherapy and use of vascular endothelial growth factor (VEGF) receptor tyrosinekinase inhibitors (13). Since there is no reported score assessing the risk of bleeding, an individual approach to assess the bleeding risk is essential when anticoagulant treatment is initiated especially in certain cancer patients, those with renal impairment, hypertension, coronary heart disease, heart failure and the very elderly (8,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In case of the Post-Marketing Safety Surveillance carried out in the USA on the basis of the data obtained from the medical database of the Department of Defense in the period from January 2013 to October 2014, in the population of 27 467 patients in whom anticoagulant treatment with rivaroxaban was used for the first time due to atrial fibrillation, major bleeding complications were reported in 2.89% of patients per year [41].…”
mentioning
confidence: 99%